Analisi della componente 3D nell'applicazione di vincoli urbanistici - Maffeis, Andrea; Caldiroli, Andrea (GEOmedia, 2015)
Some planning restrictions affecting mainly the altitude component of the buildings. In the context of Comune di Bergamo, using GIS spatial analyst tools and accurate elevation data, were studied innovative methods of analysis in the field of landscape protection and air navigation obstacles.